2019
DOI: 10.1088/2515-7620/ab3971
|View full text |Cite
|
Sign up to set email alerts
|

Extreme precipitation over East Asia under 1.5 °C and 2 °C global warming targets: a comparison of stabilized and overshoot projections

Abstract: Highly populated East Asia is vulnerable to extreme precipitation. Here, we use Community Earth System Model low-warming simulations to examine how extreme precipitation events may change in East Asia under the Paris Agreement global warming targets. The frequency and intensity of extreme precipitation will increase markedly over East Asia in the warmer climates. Limiting end-of-century warming to 1.5°C, in comparison with 2°C, will reduce the risks of extreme precipitation frequency and intensity in East Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…Both total precipitation and extreme precipitation would increase over East Asia under RCP scenarios (Kitoh et al, 2013;Li et al, 2015;Alfieri et al, 2016). The precipitation seasonal cycle would be enhanced, and a lower warming target could robustly reduce hydrological risks compared to higher warming levels (Zhang et al, 2019). Further research shows that the risk of flooding would be increasing significantly in many areas of China, especially in western China and the Huanghuai Basin .…”
Section: Accepted Articlementioning
confidence: 97%
See 1 more Smart Citation
“…Both total precipitation and extreme precipitation would increase over East Asia under RCP scenarios (Kitoh et al, 2013;Li et al, 2015;Alfieri et al, 2016). The precipitation seasonal cycle would be enhanced, and a lower warming target could robustly reduce hydrological risks compared to higher warming levels (Zhang et al, 2019). Further research shows that the risk of flooding would be increasing significantly in many areas of China, especially in western China and the Huanghuai Basin .…”
Section: Accepted Articlementioning
confidence: 97%
“…There are also a few recent studies reported in the literature (L. Chen et al, 2018, Z. Chen et al, 2020Lee et al, 2018;D. Li et al, 2019) to assess changes of the East Asian summer monsoon system in the stabilized 1.5°C and 2°C warmer worlds.…”
mentioning
confidence: 99%
“…The red '×' indicates the fidelity of the MME outputs from both the RCP4.5 and RCP8.5 scenarios were used. The Paris Agreement set a preferable target to limit global warming to 1.5 C above preindustrial levels (United Nations Framework Convention on Climate Change, 1992), and many studies have projected extreme events in models for this 1.5 C warming level (Li et al, 2019;Zhao and Zhou, 2019). Thus, for the comparison with the historical epoch , the period of 2030-2054 was chosen as the future epoch for the following analysis, during which global warming is likely to reach the 1.5 C level (IPCC SR15, 2018;Nangombe et al, 2019).…”
Section: Projection Of Ehd Characteristics Using the Optimum Modelsmentioning
confidence: 99%
“…These findings are not only pertinent to the European region but also to most of the Northern Hemisphere, including the Asian continent. However, there are relatively few published articles focussing on the understanding of large-scale circulation patterns and extreme weather events over the Asian region (Li et al 2019;Kar et al 2014).…”
Section: Introductionmentioning
confidence: 99%